The Effects of Perceived Ease of Use, Security, and Promotion on Trust and Its Implications on Fintech Adoption - Nangin, Meryl Astin; Barus, Irma Rasita Gloria; Wahyoedi, Soegeng (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2020)
The advancement of mobile devices and their usage has increased the uptake of fintech innovation. These new technologies should provide ease of use and give advantages to their customers. On the other side, mobile application security threats have increased tremendously and have become a great challenge for both users, in this case, as customers, and fintech innovators. Meanwhile, service should be promoted to the customers to establish fintech's brand to society. This research empirically examined the components affecting the expectations of users to adopt fintech. By collecting 100 samples who have already used a couple of brands of Fintech and Sakuku as their payment method, and by utilizing Structural Equation Modeling- Partial Least Square (SEM-PLS) as the technique of analysis, the empirical results definitely confirmed that perceived ease of use (PEOU) and promotion positively and significantly affected the customer trust. Meanwhile, security did not significantly affect trust. The finding also implied that in order to increase the fintech adoption rate, customer trust should be built.